2017
DOI: 10.1242/dev.150789
|View full text |Cite
|
Sign up to set email alerts
|

Defining epithelial cell dynamics and lineage relationships in the developing lacrimal gland

Abstract: The tear-producing lacrimal gland is a tubular organ that protects and lubricates the ocular surface. The lacrimal gland possesses many features that make it an excellent model in which to investigate tubulogenesis, but the cell types and lineage relationships that drive lacrimal gland formation are unclear. Using single-cell sequencing and other molecular tools, we reveal novel cell identities and epithelial lineage dynamics that underlie lacrimal gland development. We show that the lacrimal gland from its ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
31
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(71 citation statements)
references
References 47 publications
7
31
2
Order By: Relevance
“…In support of this segregation, an inverse expression profile to Krt14 was apparent for Kit expression following RA inhibition, where BMS 493 reduces expression of Kit in isolated epithelia explants (Abashev et al , 2017). In addition, KRT14 but not KIT is expressed by emerging SMA+ myoepithelial cells, which in the lacrimal gland give rise only to themselves (Farmer et al , 2017). …”
Section: Salivary Gland Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…In support of this segregation, an inverse expression profile to Krt14 was apparent for Kit expression following RA inhibition, where BMS 493 reduces expression of Kit in isolated epithelia explants (Abashev et al , 2017). In addition, KRT14 but not KIT is expressed by emerging SMA+ myoepithelial cells, which in the lacrimal gland give rise only to themselves (Farmer et al , 2017). …”
Section: Salivary Gland Developmentmentioning
confidence: 99%
“…Genetic lineage tracing has also identified the transcription factor SOX2, an essential regulator of pluripotency of embryonic stem cells (ESCs), as a marker of progenitor cells for the duct and acinar lineages in the developing SMG and SLG (PG not investigated [Emmerson et al, 2017]), as well as many other epithelial tissues (Arnold et al, 2011). We recently reported that despite SOX2 being expressed throughout the oral epithelium, SOX2 has an essential role in the generation of acini:…”
Section: Growth Factor Receptors: Kit and Lgr4/5/6mentioning
confidence: 99%
See 2 more Smart Citations
“…Based on PCA and t-SNE analyses, we identified 11 subsets within hUC-MSCs and seven subsets within hSF-MSCs. Gene set enrichment analysis determined that there were 533, 57,32, 44,10, 319, 731, 1037, 90,25 and 230 differentially expressed genes (DEGs) in the 11 subsets of hUC- MSCs and 204, 577,30, 577,16, 57 and 35 DEGs in the seven subsets of hSF-MSCs. scRNA-seq was not only able to identify subpopulations of hUC-MSCs and hSF-MSCs within the sample sets, but also provided a digital transcript count of hUC-MSCs and hSF-MSCs within a single patient.…”
mentioning
confidence: 99%